EFEKTIFITAS KONSUMSI RUMPUT LAUT UNTUK MENINGKATKAN KADAR HAEMOGLOBIN PADA IBU HAMIL ANEMIA - Rahmi, Rifa (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Hb is a red pigmented protein present in red blood cells. Increase Hb can by use Seaweed, because seaweed has a content such as iron, minerals, vitamin B complex, protein and others. The purpose of this study is to analyze the effectiveness of seaweed consumption to increase Hb levels in pregnant women. This research is Quasy Experimental research with one group pretest-posttest design with 30 maternity respondents with anemic in Lirik Community Health Centre, where the sample is taken by Purposive Sampling. Hb Pregnant women before given seaweed that the majority of respondents have Hb 8.9 gr / dl, the lowest Hb is 7 gr / dl and the highest 9.8 gr/dl. While pregnant Hb after giving the grass the majority of its Hb is 10 gr / dl, Â the highest Hb is 12.7 gr / dl and the lowest 7 gr/dl. The results showed p value <0.0001 (p <0.05) with mean change before intervention 8.94 gr / dl to 10.72 g / dl after intervention. So that seaweed is very effective in increasing Hb levels in anemic pregnant women. This suggested to pregnant women to seek their own information about the content of seaweed and also process management seaweed. This research hopefully can provide information as the development of science about the benefits of seaweed to increase Hb levels of anemic pregnant women.